Sonochemical Synthesis of Rutile Phase Copper-Doped Titanium Dioxide Coating on Fabric and Its Application in Antibacterial Testing of Staphylococcus aureus - Chew, Yi Bin; Ling, Chui Min; Koh, Pei Wen; Chew, Chee Seng; Lee, Siew Ling (Science and Technology Indonesia, 2025)
In recent years, the utilization of copper-doped titanium dioxide (Cu-TiO2) photocatalysts in antimicrobial activity has received intensive attention from researchers, especially during the COVID 19 pandemic. However, the common synthesis method of Cu-TiO2 such as the sol-gel method would not be applicable in the industrial processes because of the low production yield of the photocatalysts. Besides, anatase TiO2 is always arguable due to its high cost and less stable after a long synthesis process. Therefore, in this study, the sonochemical method was utilized to produce the Cu-TiO2 photocatalysts using TiO2 rutile as a precursor. The physicochemical properties of the synthesized photocatalysts were examined via several instrumental techniques. As evidenced by the X-ray diffraction (XRD) analysis, all the Cu-TiO2 samples were formed in the rutile phase. Diffuse reflectance ultraviolet-visible (DRUV-Vis) analysis results indicated the wavelength extension to the visible region upon Cu loading. The antibacterial properties of Cu-TiO2 photocatalysts were assessed via antibacterial testing using the Gram-positive bacteria, Staphylococcus aureus. The results indicated that the 5 mol% Cu-TiO2 achieved the highest antibacterial efficiency of 75.8% under visible light irradiation for 1 hour. The current findings suggest that the Cu-TiO2 photocatalysts could be produced via a straightforward and cost-effective synthesis method, which may continue with large-scale production and for application as an antimicrobial agent.